An evaluation of the various conservation techniques employed by selected academic institutions in Metro Manila for archival print materials - Realeza, Aileen S.; Arlante, Salvacion M. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
The study was an evaluation of the various conservation techniques employed by selected academic institutions in Metro Manila for their archival materials in paper. The institutions involved were the Ateneo de Manila University Library Archives (ADMULA), the Archives of the University of Santo Tomas (AUST), the De La Salle University Archives (DLSUA), and the University of the Philippines Archives and Records Depository (UARD).
The research study investigated the awareness of the institutions of the need and importance of a conservation program for the archives. It also sought to weigh up the status of the conservation programs and practices of the four institutions involved. It also assessed the conditions of archival print materials that they hold. The study used the descriptive case study method of research. Questionnaires and interviews were the instruments used in gathering data.
Research findings show that the four institutions have a sound conservation programs for their archives. They are aware of the need for conservation of the archives and special collections that they hold. These institutions also make sincere attempts in creating a stable and sound conservation program and practices. Only the AUST and UARD have the best preservation and restoration techniques for their archival print materials. ADMULA still experiences a lot of conservation problems, however, its conservation program is improving. It is quite near in reaching the level of stability that AUST and UARD enjoy. DLSUA on the other hand, needs to re-examine its environmental control. It also has a stable conservation program and practices; however, it still needs to straighten out serious matters like temperature and relative humidity level. It also has been found out that the archival print materials of the four institutions are relatively in good conditions. In the light of the abovementioned conclusions, this research study recommends that the institutions involved must determine the facilities and equipment lacking in the archives that they consider important in carrying out their plans of an absolute conservation program. It is also recommended to keep and increase the institutions' support to the programs of their archives. Lastly, it is recommended that the institutions use the required and time-tested preservation and restoration practices for their valuable archival collections.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Academic libraries -- Philippines -- Manila Metropolitan Area; Archival materials -- Conservation and restoration -- Philippines -- Manila Metropolitan Area; Books -- Conservation and restoration -- Philippines -- Manila Metropolitan Area